Interaction of ectoparasites-small mammals in tropical rainforest of Malaysia - Madinah, Adrus; Abang, F.; Mariana, A.; Mohd Tajuddin, Abdullah; Mohd Azlan, Jayasilan (Community Ecology Journal, 2014)
The literature regarding the diversity of ectoparasites and their interaction with their hosts remains largely inadequate in Malaysian tropical rainforest. We investigate the interaction patterns and specialization of ectoparasites infesting terrestrial small mammals (rodents and scandents) in Peninsular and Malaysian Borneo from samples made in 16 localities between 2008 and 2010. A total of 3,235 individuals of ectoparasites were collected during field surveys, resulting in an interaction network involving 47 ectoparasites that were distributed on 23 species of small mammals. The overall specialization index H2’ of all ectoparasites and host species was 0.67 which was considered moderate. Ticks appeared to be generalist with specialization index (H2’ = 0.35) while lice showed higher specialization (H2’ = 1) in selecting host species. The most diverse parasite assemblage was found on S. muelleri (Hs_w = 1.96). Specialization indices among ectoparasite species (dp) ranged from 0.03 to 1 while the indices among host species (dh) ranged from 0.20 to 1. Incomplete field data may have contributed to the high specialization indices. This study is significant as it can enhance our understanding the emergence and management of potential zoonotic diseases in Malaysia.